Field notes contributed by Joseph P. Schaufenbuel, winter 1978-1979 - Schaufenbuel, Joseph P.et al (1978)
Winter report of birds and locations contributed by Joseph P. Schaufenbuel, with additional reports from Darwin Koenig. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter 1978-1979. Epson - sheet feed/flatbed